Multiobjective Optimization of Safety Risk of Prefabricated Building Construction considering Risk Correlation. (27th April 2020) - Chang, Chunguang; Wu, Xi; Yan, Xin
Abstract : The analysis of the overall risk level of the system and the reduction of risk control costs are the key links to avoid the safety risks of prefabricated construction. In this paper, a dual-objective optimization model is constructed with the objective of minimizing system security risk loss and control cost to minimize the level of construction safety risks for prefabricated building while minimizing cost consumption. This paper introduces risk correlation into the optimization model based on the 2-additive fuzzy measure and solves it with discrete multiobjective particle swarm optimization (discrete-MOPSO). The example shows that considering the correlation of risks in different situations can better reflect the interaction relationship between the risk factors of building construction safety and improve the rationality of the optimization model.